Serosal Invasion Strongly Associated With Recurrence After Curative Hepatic Resection of Hepatocellular Carcinoma: A Retrospective Study of 214 Consecutive Cases. Issue 9 (March 2015) - Sonohara, Fuminori; Nomoto, Shuji; Inokawa, Yoshikuni; Kanda, Mitsuro; Yamada, Suguru; Fujii, Tsutomu; Sugimoto, Hiroyuki; Kodera, Yasuhiro
Abstract : Abstract: The purpose of this study was to clarify the individual prognostic factors after curative and primary resection of hepatocellular carcinoma (HCC). Reliable prognostic factors and tumor staging for HCC have been required to predict an appropriate prognosis. However, in HCC, no staging system has received universal acceptance, and several tumor factors seem to relate to HCC prognosis, but they are not definitive. At present, few studies have mentioned the importance of serosal invasion as a prognostic factor. A retrospective search of our database identified 214 consecutive patients who underwent primary and curative hepatectomy for HCC at our department between January 1998 and December 2011. Risk factors for recurrence-free survival (RFS) and overall survival (OS) were analyzed with Cox proportional hazard model, Kaplan-Meier method, and log-rank tests. Multivariate analyses showed that serosal invasion (hazard ratio [HR], 2.75; P = 0.0005) and vascular invasion (HR, 1.71; P = 0.0331) were independently correlated with RFS. Serosal invasion was significantly correlated with HCC recurrence ( P = 0.0230). The Kaplan–Meier method and log-rank tests revealed that the patients with serosal invasion showed significantly worse prognosis both in RFS ( P < 0.0001) and OS ( P = 0.0016). Serosal invasion should be regarded as a strong independent predictor for recurrence in curatively resected HCC cases. Abstract : Supplemental Digital Content is available in the text